DEVELOPMENT OF A PANCASILA-BASED COMMUNAL IPR LEGAL SYSTEM IN THE GLOBALIZATION ERA - Dina Haryati Sukardi Dina; Rohaini Rohaini (Law Faculty of Universitas Bandar Lampung, 2023)
Traditional knowledge is an embodiment of a tradition in each country, traditional knowledge in Indonesia must be in accordance with and in line with the values contained in the ideology of Pancasila as the basis for living as a nation state in Indonesian society, the problem in this paper is how the values of Pancasila are contained in the study of knowledge traditional. Pancasila as the basis of the state implies that Pancasila is used as the basis for administering the state. Pancasila as the basis of the state means that the entire implementation and administration of government must reflect the values of Pancasila and must not conflict. The values in a traditional knowledge are actually in harmony with the values contained in Pancasila.